If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + -1(-2) = 4 Multiply -1 * -2 t + 2 = 4 Reorder the terms: 2 + t = 4 Solving 2 + t = 4 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + t = 4 + -2 Combine like terms: 2 + -2 = 0 0 + t = 4 + -2 t = 4 + -2 Combine like terms: 4 + -2 = 2 t = 2 Simplifying t = 2
| 35(2x-1)=7(x+4)+3x | | c(c+2)-5=b(x-3) | | x(x+2)+x=6 | | c(x+2)-5=c(dx-2) | | 4b+5=3b-9 | | 2(x-1)-3(x+2)=3x+4 | | -14+x=x+15 | | 7x-4y=-12 | | 7(3-x)=21 | | 2(a-4)=6 | | 6-4(r+2)=-37+r | | h=vt-5t^2 | | s^3-q^3= | | 0.3x=3 | | 12x-3y=6 | | 6x-3+3x=24 | | 8r-18=-74+r | | .50x+13=9 | | t^3+7t^2-4t-28=0 | | 1.3(8-b)+3.7b=5.2 | | -128a^2+98= | | -6n-(n-1)=-6n+6 | | 0.6t-4=2 | | 3(5c+4d)+6(d-2c)= | | X^2-19+90=0 | | .08=7.50+5x | | 72=-8(4a-5) | | 6x^2+36x-42=0 | | 2x+2=129 | | 9x+2x+6-x=10 | | 4b+4=4(1+2b)-8 | | 35(2x-1)=7(x-4)+3x |